2009
DOI: 10.1007/s10490-009-9180-1
|View full text |Cite
|
Sign up to set email alerts
|

Family ownership and firm performance: Influence of family management, family control, and firm size

Abstract: This study examines the relationship between family ownership and firm performance by considering the influence of family management, family control, and firm size. Using proxy data of 786 public family firms in Taiwan during 2002-2007, this study found that family ownership is positively associated with firm performance. The positive association is strong particularly when family members serve as CEOs, top managers, chairpersons, or directors of the firms; however, the association becomes weak when family mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
172
0
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(214 citation statements)
references
References 52 publications
18
172
0
17
Order By: Relevance
“…Stewardship behaviour (Eddleston and Kellermanns, 2007;Eddleston, Kellermanns and Zellweger, 2012) is entirely consistent and supportive of corporate citizenship behaviour. Particularly with the family modelling citizenship behaviour at the top, it can be logically argued that this will support stewardship and corporate citizenship behaviour in the rest of the firm (Chu, 2011). Furthermore, family businesses have been reported to be concerned with long-term survival and such a long-term orientation produces multiple attitudes and behaviours (futurity, continuity, persistence, intertemporal choice and self-control to name a few) consistent with corporate citizenship behaviour (Lumpkin, Brigham and Moss, 2010).…”
Section: Business-centred Goals and Corporate Citizenship Behaviourmentioning
confidence: 99%
“…Stewardship behaviour (Eddleston and Kellermanns, 2007;Eddleston, Kellermanns and Zellweger, 2012) is entirely consistent and supportive of corporate citizenship behaviour. Particularly with the family modelling citizenship behaviour at the top, it can be logically argued that this will support stewardship and corporate citizenship behaviour in the rest of the firm (Chu, 2011). Furthermore, family businesses have been reported to be concerned with long-term survival and such a long-term orientation produces multiple attitudes and behaviours (futurity, continuity, persistence, intertemporal choice and self-control to name a few) consistent with corporate citizenship behaviour (Lumpkin, Brigham and Moss, 2010).…”
Section: Business-centred Goals and Corporate Citizenship Behaviourmentioning
confidence: 99%
“…Furthermore, in small businesses controlled by their owners, profitability is not a strong enough incentive for management to participate in the company's capital (Stewart et al, 2001). Schulze et al (2001) and Chu (2011) suggest that the agency costs incurred by small businesses are related to the altruistic feelings of the owners as family management, constituting a strong incentive to promote and sustain family ties. Our results are in line with those obtained by Schulze et al (2001) and Steier (2003); however, they contradict those reported by Littuen (2000) and Chung and Chan (2012) who found performance had a positive effect on managerial ownership.…”
Section: Ii) Managerial Ownership Versus Operational Performancementioning
confidence: 99%
“…The models are built by using Generalised Least Squares (GLS) and Ordinary Least Squares (OLS) regressions. By referring to the literature in this area (Anderson & Reeb, 2003;Maury, 2006;Chu, 2009), our first equation measures the effect of family ownership on performance and is formulated as follows: Pieper et al, (2008) and Villalonga and Amit (2006), the age for each company is defined as the natural logarithm of the number of years since its creation. Debts i,t is a variable to control for the effect of capital structure on performance.…”
Section: Modelsmentioning
confidence: 99%